Powder Metallurgy Processing of Ti-Nb Based Biomedical Alloys - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2018)
New Ti based alloys with non-cytotoxic and biocompatible elements, such as Nb, Zr, Ta, Sn and Mo, have recently attracted much attention for orthopedic applications. The aim of this study was to investigate the effects of Sn content (2 and 4 wt%) on microstructure and mechanical properties of Ti16NbXSn sintered alloys. The results indicated that Ti16Nb(0-4) Sn alloys were composed of alpha + beta phases. Hardness and Young's modulus E of the alloys measured using nanoindentation technique. These results show that there is a relationship between the mechanical properties and Nb-Sn content. It is concluded that addition of Nb to the cp-Ti resulted to a decrease in Young's modulus.
Keywords: powder metallurgy; TiNbSn alloys; implant; MECHANICAL-PROPERTIES